Investigation on the Incidence of Syncope in Children and Adolescents Aged 2–18 Years in Changsha - Hu, Erlin; Liu, Xiaoyan; Chen, Qianqian; Wang, Cheng (Frontiers in Pediatrics, 2021)
Objectives: Syncope is common clinically, but there is lack of literature on childhood morbidity. This article will make cross-section survey the incidence of syncope in children and adolescents aged 2-18 years in Changsha. Materials and Methods: 4352 children and adolescents aged 2-18 years were randomly selected from 6 primary and secondary schools and 3 kindergartens in Changsha from March 2018 to November 2018. 4916 standardized questionnaires were distributed, and 4352 (88.53%) valid questionnaires were recovered. Results: (1) Incidence: 17.37% children and adolescents aged 2-18 years who had more than one syncope, the incidence in the adolescence (28.85%) was higher than that in the school age (8.32%) and in the preschool age (2.71%) (P<0.01). (2) Age of Onset: 13.9±3.1 years, with a peak age of 16 years. (3) Gender Difference: The incidence of adolescence females was higher than that in males (31.72% vs. 26.25%, P<0.05). Gender differences: inducements: Females in sweltering environment were higher than males (P<0.01), while males in urination were higher than females (P<0.05). presyncope: Dizziness, nausea, sweating and facial pallor were higher in females than males (P<0.05). Conclusions: The incidence of syncope in children and adolescents aged 2-18 years in Changsha is17.37%. The incidence of syncope is different between males and females in different age groups, and there is gender difference in syncope inducements and presyncope.